2013
DOI: 10.1371/journal.pone.0055116
|View full text |Cite
|
Sign up to set email alerts
|

Occludin Is Involved in Adhesion, Apoptosis, Differentiation and Ca2+-Homeostasis of Human Keratinocytes: Implications for Tumorigenesis

Abstract: Tight junction (TJ) proteins are involved in a number of cellular functions, including paracellular barrier formation, cell polarization, differentiation, and proliferation. Altered expression of TJ proteins was reported in various epithelial tumors. Here, we used tissue samples of human cutaneous squamous cell carcinoma (SCC), its precursor tumors, as well as sun-exposed and non-sun-exposed skin as a model system to investigate TJ protein alteration at various stages of tumorigenesis. We identified that a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 74 publications
2
52
1
Order By: Relevance
“…It is likely that the noted discrepancies in cellular localization associated with the different antibodies arise from the differences in epitope specificity. In several studies [32,64], other markers for adult keratinocytes were used, such as CK5 and E-Cadherin; however, we were unable to evaluate the expression of these markers in or on our equine EpSCs or their differentiated progeny, due to a lack of crossreactivity of several commercially available antibodies tested (data not shown). In this regard, it has been reported that only about 4% of human antibodies reacts with the equivalent equine epitopes [65].…”
Section: Discussionmentioning
confidence: 98%
“…It is likely that the noted discrepancies in cellular localization associated with the different antibodies arise from the differences in epitope specificity. In several studies [32,64], other markers for adult keratinocytes were used, such as CK5 and E-Cadherin; however, we were unable to evaluate the expression of these markers in or on our equine EpSCs or their differentiated progeny, due to a lack of crossreactivity of several commercially available antibodies tested (data not shown). In this regard, it has been reported that only about 4% of human antibodies reacts with the equivalent equine epitopes [65].…”
Section: Discussionmentioning
confidence: 98%
“…Subsequent to RCM imaging, the constructs were snap frozen, sectioned into 5 μm slices (Leica CM 1510S; Wetzlar, Germany), and analyzed by hematoxylin-eosin and immunofluorescence staining. Tight junction proteins were analyzed from paraffinembedded constructs as described [19]. Pictures were taken with a fluorescence microscope (BZ-8000, Keyence; Neu-Isenburg, Germany or Axiophot II, Zeiss; Göttingen, Germany), and analyzed with Openlab 2.0.9 or ImageJ software.…”
Section: Morphology and Immunofluorescencementioning
confidence: 99%
“…Cells with strong b-catenin and ZO-1 expression were found in the skin of HPV8 transgenic mice and EV lesions, which supports a possible clinical relevance of our data. A broader expression pattern of ZO-1 in epidermal layers has previously been shown in skin SCC, which suggests that ZO-1 contributes to tumour progression, largely in a tight junction independent manner (Brandner et al, 2015;Hintsala et al, 2013;Kirschner & Brandner, 2012;Morita et al, 2004;Rachow et al, 2013). In melanoma cells, an increase of ZO-1 mRNA and protein levels was observed compared to normal melanocytes.…”
Section: Discussionmentioning
confidence: 81%